GERAKAN KESETARAAN GENDER ANTARA MODERATISME ISLAM DAN RADIKALISME BARAT - Titis Rosowulan (Wahana Islamika: Jurnal Studi Keislaman, 2017)
Equality of position is the right of every person, including women. In historical records, women are very vulnerable to facing injustice which results in their rights being harmed. As a result, the position of women becomes marginalized and even their position becomes subordinated. To respond to this gender injustice, various movements emerged that sought to minimize the margin of injustice. Unfortunately, this kind of movement is sometimes too excessive, so it keeps women away from their natural nature. This article seeks to compare the views of the gender equality movement between western radicalism which in fact distracts women from their nature and moderate views of Islam which places women in their natural nature. this study was examined qualitatively with a comparative approach. This study concluded that the gender equality movement proposed by western radicals actually led women to new problems that could not balance rights and obligations. While the equality movement proposed by moderate Muslims seeks to place women's rights and obligations in a balanced manner, so as not to cause new problems rooted in the imbalance of rights and obligations